Evaluation of genetic diversity of 12 gerbera varieties (Gerbera L.) based on morphology and RAPD marker - Nguyen, Tuyet Anh; Tran, Thi Thuy Duong; Quan, Ngoc Giau; Le, Van Thuc; Trinh, Ngoc Ai (Hue University Journal of Science: Natural Science, 2025)
This study focuses on evaluating the genetic diversity of 12 Gerbera varieties from farms in Da Lat city (Lam Dong province) based on 9 morphological characteristics and 10 RAPD primers. A higher different level between varieties was observed by using RAPD markers compared to morphological markers. A total of 110/135 polymorphic bands were generated, which occupied 12.2%. The average of PIC and Rp value are 0.48 and 11.39, respectively. The genetic similarity coefficient based on morphological analysis and RAPD data was 0.98-0.99 and 0.46-0.82, respectively, which showed that RAPD primers are useful for detecting genetic polymorphism. The results from morphological data showed that XB, HX and DX2 varieties are suitable for the cut flower market; meanwhile, DD1 and DD2 varieties are characterized by large flower size, DD2 and DX2 have long and wide petals. The RAPD analysis results indicated that OPE02, OPE08 and OPE13 generated a high polymorphic rate (100%), while OPG16 primer showed the lowest polymorphism percentage (52.9%). This study demonstrates that the combination of phenotypic and genotypic methods provides valuable insights into the understanding of genetic diversity among species.